2009
DOI: 10.4067/s0717-95022009000300032
|View full text |Cite
|
Sign up to set email alerts
|

Dextrocardia and Situs Inversus Totalis in a Nigerian Cadaver: A Case Report of Rare Anomaly

Abstract: SUMMARY:This report describes an adult male cadaver with dextrocardia and situs inversus totalis in a Nigerian cadaver. The photographic illustrations revealed transposition of some of the visceral organs such that the stomach and spleen were located on the right and the liver and gall bladder on the left. Also, the left lung was tri-lobed while the right was uni-lobed. The heart was flattened and flipped to the right thus, transposing the great vessels. The report showed that dextrocardia and situs inversus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A variety of secondary metabolites such as tannins, terpenoids, alkaloids, flavanols, phenols, glycosides are present in cashew leaf [65]. It has been also reported that Cashew contains gallic acid, anacardic acid, anacardol, hydroxyl benzoic acid, capryllic acid, gadoleic acid, lauric acid, leucine, leucocyanides, ocimene, limonene, caryophyllene and alpha cadinene [24,70]. The FTIR spectrum of Au NPs (Fig.…”
Section: Ftir Studiesmentioning
confidence: 95%
“…A variety of secondary metabolites such as tannins, terpenoids, alkaloids, flavanols, phenols, glycosides are present in cashew leaf [65]. It has been also reported that Cashew contains gallic acid, anacardic acid, anacardol, hydroxyl benzoic acid, capryllic acid, gadoleic acid, lauric acid, leucine, leucocyanides, ocimene, limonene, caryophyllene and alpha cadinene [24,70]. The FTIR spectrum of Au NPs (Fig.…”
Section: Ftir Studiesmentioning
confidence: 95%
“…One such non-cardiac malformation is the combination of dextrocardia, abnormality of mucociliary function and bronchiectasis (Kartagener's syndrome) which has been reported in a Nigerian child and is associated with repeated sinus and pulmonary infections. 2 Several cases of dextrocardia have been documented in Nigeria, some with co-existing cardiac anomaly while others were asymptomatic or had non cardiac symptomatic malformations [10][11][12][13][14] The recognition of situs inversus is important for preventing surgical mishaps that result from the failure to recognize reversed anatomy or an atypical history. For example, in a patient with situs inversus, cholecystitis typically causes left upper quadrant pain 15 Situs inversus also complicates organ transplantation operation as donor organs will almost certainly come from situs solitus (normal), as heart and liver have geometric problems while placing the organs into a cavity shaped in mirror image.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the heart forming in the fetus on the left side, it flips over and forms on the right side 1 Situs inversus (also called situs transversus) is a congenital condition in which the major visceral organs are reversed or mirrored from their normal positions. Many people with situs inversus totalis are unaware of their unusual anatomy until they seek medical attention for an unrelated condition 1 Dextrocardia is frequently diagnosed in a routine prenatal sonogram, although not every radiologist will identify it, particularly if there are no cardiac structural abnormalities 2 Diagnostic modalities like a chest radiograph and an electrocardiogram are sufficient to make a diagnosis of dextrocardia while more recent imaging modalities like echocardiography and magnetic resonance imaging puts the diagnosis beyond doubt. We report a peculiar case of dextrocardia with situs inversus in a 69 year old woman whose chest radiograph was erroneously labelled by the radiographer as normal.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis can be made through clinical evaluation, electrocardiogram (ECG), chest X-ray and abdominal ultrasonography, echocardiography and computed tomography (CT) [35]. In a few cases, diagnoses were made at autopsy or during dissection of cadavers [6, 7]. This case illustrates the role of an ECG in the diagnosis of dextrocardia.…”
Section: Introductionmentioning
confidence: 99%